Islamization of the Discipline of Education (American Journal of Islam and Society, 1989)
I. The Concept of the Discipline of EducationA. Fields of knowledge are diversified, and touch upon almostevery aspect of life and the universe, including the physical,societal, spiritual and material aspects. Various theories ofknowledge are proposed by man to deal with its classification,acquisition and use in life situations. The discipline ofeducation deals with the question of teaching and learningof various disciplines of knowledge by teachers and studentswith the hope of changing the behavior of the learner to adaptto society and develop the capabilities necessary to becomean effective human being.Education, then, is an applied discipline of knowledge whichis a composite of other social and humanistic disciplines.It concerns itself with changing the behavior of the learner,in terms of information, skills and attitudes. Education guideshuman beings in a certain direction delineated by the valuesof the society or a certain ideology using know-how, methods,and technologies of teaching compatible with their natureand style of learning.Education, then, is both a process and a result of a process.The results or objectives of education reflect the dimensionalvalue system of the society, and thus education is never aneutral discipline. Education cannot be neutral since itproduces an individual with a personality that represents thevalue system of the society and its ideology in life. The contentof the educational discipline depends on its interaction withother social and humanistic disciplines which are also partlyvalue oriented and partly experimentally oriented. The processof education or the know-how, including use of methods, ...